The "strength of weak ties" and helminth parasitism in giraffe social networks. (18th March 2016) - VanderWaal, Kimberly L.; Obanda, Vincent; Omondi, George P.; McCowan, Brenda; Wang, Hui; Fushing, Hsieh; Isbell, Lynne A.
Lay Summary: Contact outside one's social clique or "weak ties" are almost entirely ignored in studies of social behavior and parasitism in wildlife, even though weak ties are a ubiquitous feature of the social systems of many species, including humans. Here, we show that "socially adventurous" giraffes, who frequently interact with individuals outside their core social clique and maintain population-level social connectivity, are critical for the spread of disease because they are more likely to be infected with parasites. Twitter: @KVanderWaal9 Abstract: The so-called "strength of weak ties" is a central concept in social network theory, especially for understanding how information and diseases are transmitted through socially structured populations. In general, weak ties occur in networks where relatively few individuals are responsible for maintaining linkages between groups of individuals that would otherwise be poorly connected. This common structural motif can be seen in the social networks of species with fission–fusion social organization, such as giraffe ( Giraffa camelopardalis ). Giraffe social networks are characterized by social cliques in which individuals associate more with members of their own social clique than with those outside their clique. Individuals involved in weak, between-clique social interactions are hypothesized to serve as bridges by which an infection may enter a clique and, hence, may experience higher infection risk. Here, we address this and other hypotheses explaining helminth infection patterns in wild giraffe, exploring the relative roles of the social network and ranging behavior in determining infection risk. We show that infection risk is more influenced by weak ties with individuals outside one's clique than by repeated contact with a core set of associates. Even when controlling for age and home range size, individuals who engaged in more between-clique associations, that is, those with multiple weak ties, were more likely to be infected with gastrointestinal helminth parasites. Our results suggest that diverse social interactions with giraffe from multiple cliques may increase exposure to pathogens. The importance of weak ties in pathogen transmission has only rarely been empirically demonstrated in wildlife.